2015
DOI: 10.4149/bll_2015_138
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of appendix pathology: irregular distribution of myenteric ganglia in human appendiceal wall

Abstract: OBJECTIVES: Although appendicitis is a common disease, basic questions about risk factors and its etiology remain unexplained. BACKGROUND: An obstruction of the appendix lumen is usually considered to be the main cause of acute appendicitis. However, more studies are currently dealing with neuroimmune appendicitis. METHODS: We studied samples of human appendices with the histological diagnosis of chronic appendicitis. Fixed cryosections of appendiceal walls were examined by immunofl uorescence methods using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the other hand, only several reports with confl icting results are dealing with myenteric ganglia in human appendix. Recently we described the irregular distribution of myenteric ganglia in human appendix (13) and the presence of myenteric ganglia in the subserosal area which occured more frequently in appendices with diagnosis of chronic appendicitis (8). Irregular distribution of myenteric ganglia was described in some studies (14,15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, only several reports with confl icting results are dealing with myenteric ganglia in human appendix. Recently we described the irregular distribution of myenteric ganglia in human appendix (13) and the presence of myenteric ganglia in the subserosal area which occured more frequently in appendices with diagnosis of chronic appendicitis (8). Irregular distribution of myenteric ganglia was described in some studies (14,15).…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies revealed that the obstruction is not a causative factor of acute appendicitis (6, 7). Recently, we described the atypical myenteric ganglia distribution in relation to appendix pathology (8). Here, we examined the co-expression of neuronal and glial markers in normal human appendiceal wall.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to HSCR, an altered distribution of intramural ganglia has been found in the appendices of AA patients (Kubikova et al, 2015). Furthermore, up to 50% of HSCR patients are suffering from a recurrent colitis that also persists after resection of the aganglionic colon segment in about half of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genome‐wide association studies (GWAS) found strong association of appendectomies with a SNP near PITX2 (Kristjansson et al, 2017), a gene also involved in intestinal development that has been shown to be significantly less expressed in appendectomy specimen (Orlova et al, 2019). Recent studies also showed an irregular distribution of ganglia in the wall of inflamed appendices, suggesting a possible role of ganglia cell distribution and functioning in the pathogenesis of AP similar to HSCR (Kubikova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%